RE-WRITTEN FROM MEMORY - IN SLOW MOTION OF RENATO TAPAJÓS:: BETWEEN TESTIMONY AND AUTOFICTION - de Figueiredo Fiuza, Adriana Aparecida; Giordani, Rosselane Liz (fólio - revista de letras, 2019)
In order to reveal his experience of opposition militancy to the Brazilian dictatorship during the 1960s, Renato Tapajós publishes Em câmara lenta (1977), a work that brings to the heart of the discussions the relations between literature, history, memory, autofiction. The article aims to problematize the issues pertinent to the writing process of the novel, presenting a reading from the theories of Álvarez Fernández, Paul Ricouer and Márcio Seligmann-Silva about the testimony and of Alicia Molero de la Iglesia and Anna Faedrich Martins about the autofiction.